Enantioselective degradation of ofloxacin and levofloxacin by the bacterial strains Labrys portucalensis F11 and Rhodococcus sp. FP1 - Maia, Alexandra S. (2018)
Fluoroquinolones are a class of antibiotics widely prescribed in both human and veterinary medicine of high environmental concern and characterized as environmental micropollutants due to their ecotoxicity and persistence and antibacterial resistance potential. Ofloxacin and levofloxacin are chiral fluoroquinolones commercialized as racemate and in enantiomerically pure form, respectively. Since the pharmacological properties and toxicity of the enantiomers may be very different, understanding the stereochemistry of these compounds should be a priority in environmental monitoring. This work presents the biodegradation of racemic ofloxacin and its (S)-enantiomer levofloxacin by the bacterial strains Labrys portucalensis F11 and Rhodococcus sp. FP1 at a laboratory-scale microcosm following the removal and the behavior of the enantiomers. Strain F11 could degrade both antibiotics almost completely when acetate was supplied regularly to the cultures. Enrichment of the (R)-enantiomer was observed in FP1 and F11 cultures supplied with ofloxacin. Racemization was observed in the biodegradation of the pure (S)-ofloxacin (levofloxacin) by strain F11, which was confirmed by liquid chromatography - exact mass spectrometry. Biodegradation of ofloxacin at 450 μg L−1 by both bacterial strains expressed good linear fits (R2> 0.98) according to the Rayleigh equation. The enantiomeric enrichment factors were comprised between −22.5% to −9.1%, and −18.7% to −9.0% in the biodegradation of ofloxacin by strains F11 and FP1, respectively, with no significant differences for the two bacteria under the same conditions. This is the first time that enantioselective biodegradation of ofloxacin and levofloxacin by single bacteria is reported.